The Mosque Management Revitalization Through Economic Empowerment of Ummah - Moh. Arifin; Ridan Muhtadi; Tate Agape Bawana (International Journal of Islamic Thought and Humanities, 2024)
This study aims to enhance the role of the mosque's function as a religious institution so that it is not only used for the spiritual welfare of the community but also must be able to prosper economically. This study adopts a qualitative approach with the phenomenology study method and combines analysis techniques of reduction, display, and verification. The object of this research is the Jenderal Sudirman mosque, Surabaya, where the collection of data comes from observation, in-depth interviews, and documentation. The results of the study show that the application of inputs (institutional, leadership, and goals), processes (spiritual formation, personal mental formation, capacity building, and empowerment), outputs (strengthening of character, strengthening of emotional relationships, strengthening of business and strengthening of the economy and outcomes ( spiritual ability and financial ability)) in economic empowerment is still suboptimal. Therefore, mosques need to revitalize their management to collaborate with the government, state or private universities, private institutions or institutions, and the community. Moreover, the mosque should not only be prospered by the ummah; conversely, it can also prosper the ummah.